Membrane technology for CO2 removal from CO2 rich natural gas - Shovon, Shaik Muntasir; Akash, Faysal Ahamed; Monir, Minhaj Uddin; Ahmed, Mohammad Tofayal; Azrina, Abd Aziz (Elsevier, 2024)
The membrane gas separation technique is widely used across the world for gas separation, air purification, and CO2 exclusion, among other approaches. Membrane can be used for separating toxic air and water. Small size, diversity, maintenance, and simplicity are the advantages of membrane. Several challenges of membrane gas separation and its development and purification processes are reviewed. Current application of membrane (biogas enrichment, air purification, CO2 removal, hydrogen recovery) is also discussed in this chapter. The difficulty of removing CO2 and other contaminants is pointed out systematically. Besides polymeric membranes, solution-diffusion is the most suitable procedure for removing CO2. Moreover, future prospects of membrane gas separation technology are reviewed briefly. The ultimate goal is to provide information on numerous mechanisms for gas transportation application of membrane gas separation. Therefore, the outcome of this chapter is also utilized to develop new materials for better gas separation and to cover gaps in membrane gas separation technology.